Single-dose Acute Toxicity of 4-F-MDMB-BUTINACA Designer Cannabis Drug: LD50 and Histological Changes in Mice - Elkhatim H. Abdelgadir ElAmin; Renad H. F. Albloi; Abdulsallam Bakdash; Sachil Kumar (Indian Journal of Forensic Medicine & Toxicology, 2022)
The purpose of this research was to evaluate the single-dose toxicity of 4-F-MDMB-BUTINACA in Swiss albinomice using histopathological analysis of liver and kidney specimens.The experimental protocol included oral treatment of mice with different doses (5, 50, 300, 2000 mg/kg bodyweight of 4-F-MDMB-BUTINACA) for 24 hours. At the end of the treatment, blood samples had been drawn, andrenal and hepatic tissues have been excised from the experimental mice groups for histological examinations.The results revealed that dose-dependent treatment with 4-F-MDMB-BUTINACA causes mild tremor clinicalsigns with low doses and photophobia (sensitivity to light) and even cessation of breathing as a potential cause ofdeath with high doses in treated mice.The LD50 value of 4-F-MDMB-BUTINACA was 32.60 mg/kg, which is considered as a chemical compound of lowtoxicity. Histological studies confirmed that liver and kidney toxicities have been manifested in the findings ofcongestion, necrosis, inflammation, and bleeding within the liver and to lesser extent in the kidneys.